Energia elétrica como vetor de desenvolvimento rural: estudo de casos no Estado da Bahia - Leal, Edson Luiz (2008)
This paper relates to the importance of the electric power supplying for the sustainable development of the poor rural population. The main objective is to analyze the outcomes of the Programa Luz para Todos - LPT program, so far. It is expected to be a quantitative and qualitative analysis. The quantitative analysis of the LPT program was based on the rural electrification goals established for several regions in Brazil as well as on the goals agreed with between ANEEL National Agency for Electric Power Regulation and several power utilities in Brazil northeastern and northern regions. On the other hand, the qualitative analysis was held taking in consideration the premises of this program whose core is the rural electrification integrated with other rural development policies. Also, a critical analysis of the main programs of rural electrification implemented by the end of the nineties in Bahia State was made. The lack of interest in rural electrification, the ineffectiveness of the public sector, the high cost of the access to electric power, not viable for poor population, the geographical characteristics of the Bahia State, the non utilization of modern technologies and the non existence of specific regulations for the rural sector are aspects which are considered by many as causes for the slow rhythm of such programs, in this period The complete legal and regulatory context regarding to electric power universalization has been visited. Also, decentralized systems were approached, with emphasis in concepts, advantages and disadvantages of each renewable energy source, with demonstration of their uses. The methodology used in these procedures was bibliographical and documental researches, collection of information in interviews, case studies and application of questionnaires. As a conclusion, this paper demonstrates that the main objective of the LPT program in Bahia is being satisfactorily accomplished because over 7 million of rural customers have been connected to the power system by December 2007, out of 10 million rural customers expected to connect by 2008, so assuring their access to the electric power services. Although many persons in bad social and economical conditions have been benefited with the LPT Program, the government initiatives for the sustainable development of rural population are still very punctual.